Expression of HOTAIR and PTGS2 as potential biomarkers in chronic myeloid leukemia patients in Brazil - Kubaski Benevides, Ana Paula; Marin, Anelis Maria; Wosniaki, Denise K.; Oliveira, Rafaela Noga; Koerich, Gabriela Marino; Kusma, Bianca Nichele; Munhoz, Eduardo Cilião; Zanette, Dalila Luciola; Aoki, Mateus Nóbrega (Frontiers in Oncology, 2024)
Chronic myeloid leukemia (CML) is a clonal myeloproliferative neoplasm in which all the patients has the translocation (9;22) that generates de BCR::ABL1 tyrosine kinase. Despite this disease possessing a good biomarker (BCR::ABL1 transcripts level) for diagnosis and prognosis, many studies has been performed to investigate other molecules, such as the long noncoding RNAs (lncRNAs) and mRNAs, as potential biomarkers with the aim of predicting a change in BCR::ABL1 levels and as an associated biomarker. A RNAseq was performed comparing 6 CML patients with high BCR::ABL1 expression with 6 healthy control individuals, comprising the investigation cohort to investigate these molecules. To validate the results obtained by RNAseq, samples of 87 CML patients and 42 healthy controls were used in the validation cohort by RT-qPCR assays. The results showed lower expression of HOTAIR and PTGS2 in CML patients. The HOTAIR expression is inversely associated with BCR::ABL1 expression in imatinib-treated CML patients, and to PTGS2 showing that CML patients with high BCR::ABL1 expression showed reduced PTGS2 expression.